Pengaruh Model Directed Listening and Thingking Activity Berbantuan Media DASBO Terhadap Keterampilan Menyimak Siswa SD - Khoirunnisa; Hawa, Anni Malihatul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
ABSTRACT Listening skill is one of the essential language skills in elementary education, as it plays a crucial role in supporting students’ learning processes. However, the listening skills of second-grade elementary school students are still relatively low, indicating the need for learning models and instructional media that can enhance students’ engagement in listening activities. This study aimed to determine the differences and the effect of the Directed Listening and Thinking Activity (DLTA) learning model assisted by Daily Spin Board (DASBO) media on the listening skills of second-grade elementary school students. This study employed a quantitative approach with a quasi-experimental method using a pretest-posttest control group design. The research subjects consisted of second-grade students of SD Negeri Pringapus 01 as the experimental group and SD Negeri Pringapus 03 as the control group. Data were collected through listening skill tests, questionnaires, and observations. The data were analyzed using normality tests, homogeneity tests, independent sample t-tests, and coefficient of determination tests. The results showed that the average posttest score of students’ listening skills in the experimental group was 67.11, while the control group obtained an average score of 52.41. The independent sample t-test revealed a significance value of 0.000 < 0.05, indicating a significant difference between the experimental and control groups. Furthermore, the linear regression analysis showed an R² value of 0.264, meaning that the DLTA learning model assisted by DASBO media contributed 26.4% to the improvement of students’ listening skills. Therefore, the DLTA learning model assisted by DASBO media has a positive and significant effect on the listening skills of second-grade elementary school students and can serve as an effective and innovative alternative for classroom instruction. Keywords: Directed Listening and Thinking Activity (DLTA), Daily Spin Board (DASBO), Listening Skills, Elementary School Students. ABSTRAK Keterampilan menyimak merupakan salah satu keterampilan berbahasa yang berperan penting dalam proses pembelajaran di sekolah dasar. Namun, keterampilan menyimak siswa kelas II masih tergolong rendah sehingga diperlukan model dan media pembelajaran yang mampu meningkatkan keterlibatan siswa dalam kegiatan menyimak. Penelitian ini bertujuan untuk mengetahui perbedaan dan pengaruh model pembelajaran Directed Listening and Thinking Activity (DLTA) berbantuan media Daily Spin Board (DASBO) terhadap keterampilan menyimak siswa kelas II sekolah dasar. Penelitian ini menggunakan metode kuantitatif dengan desain quasi experiment jenis pretest-posttest control group design. Subjek penelitian terdiri atas siswa kelas II SD Negeri Pringapus 01 sebagai kelas eksperimen dan siswa kelas II SD Negeri Pringapus 03 sebagai kelas kontrol. Teknik pengumpulan data menggunakan tes keterampilan menyimak, angket, dan observasi. Data dianalisis melalui uji normalitas, uji homogenitas, uji independent sample t-test, dan uji koefisien determinasi. Hasil penelitian menunjukkan bahwa rata-rata nilai posttest keterampilan menyimak siswa pada kelas eksperimen sebesar 67,11, sedangkan pada kelas kontrol sebesar 52,41. Hasil uji independent sample t-test menunjukkan nilai signifikansi sebesar 0,000 < 0,05, sehingga terdapat perbedaan yang signifikan antara kelas eksperimen dan kelas kontrol. Selain itu, hasil uji regresi linear menunjukkan nilai R² sebesar 0,264, yang berarti model pembelajaran DLTA berbantuan media DASBO memberikan kontribusi sebesar 26,4% terhadap peningkatan keterampilan menyimak siswa. Dengan demikian, model pembelajaran DLTA berbantuan media DASBO berpengaruh positif dan signifikan terhadap keterampilan menyimak siswa kelas II sekolah dasar serta dapat dijadikan sebagai alternatif pembelajaran yang efektif dan inovatif. Kata Kunci: Directed Listening and Thinking Activity (DLTA), Daily Spin Board (DASBO), keterampilan menyimak, sekolah dasar.